Cytogenetic findings indicate heterogeneity in patients with blepharophimosis, epicanthus inversus, and developmental delay. Issue 1 (January 1995) - Warburg, M; Bugge, M; Brøndum-Nielsen, K
Abstract : Three unrelated, mentally retarded boys with typical blepharophimosis-ptosis-epicanthus inversus syndrome (BPES) were found to have chromosomal aberrations. One of them had a del(3)(p25), another patient had a de novo translocation t(2; 3), which after high resolution banding combined with chromosome painting was interpreted to be unbalanced with a loss of band q23. The third patient had a del(7)(q34). The phenotypes of the two patients with chromosome 3 related syndromes were similar, but the third also had genital malformations resembling the Smith-Lemli-Opitz syndrome. This patient had a palatal ridge, and a single mesial maxillary tooth suggesting the holoprosencephaly sequence, but CT scans of the brain were normal.